Optimization Chicken Bones Gelatin Extraction Using Hydrochloric Acid Immersion and Multi-Stage Thermal Treatment - Deva Krisna Kadarani; Akyunul Jannah (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2022)
The growing poultry consumption rate yearly includes chicken with significantly increased amounts of by-products like skin and bones. Chicken bones are unused properly even if the bone is rich in collagen which is the primary material to produce gelatin. Gelatin usually is generated by bovine and porcine, but some health and religious issues have successfully forbid using both resources. Chicken bones could be an alternative material for gelatin production. This research aimed to investigate chicken bones as a substitute resource for gelatin manufacturing using hydrochloric acid submersion in collaboration with multi-stage thermal treatment. Chicken bones were proceeded in several steps such as degreasing, decontamination, resizing, demineralization using a hydrochloric acid immersion (1.50, 3.00, 4.50, and 6.00% v/v) for 24 and 48 hours, addition gelatin extraction using multi-stages thermal process (55, 65, and 75°C) for 4 hours each temperature subsequentially, evaporating, drying, and shaping a gelatin powder. This study produced type A gelatin which investigated yield number, moisture and ash content, gel strength, acidity level, and functional group using Fourier-transform Infrared (FTIR) spectroscopy. The sample gelatin has obtained at least 2% up to 8% yields. The moisture and ash contents were suitable to the commercial specification range, 4-12%, and 0.1-0.4%, respectively. The acid conditioning process has an impact on acidity with pH levels 4.40-5.44. Based on gelatin standards, this study declared that processing chicken bones using 6.00% hydrochloric acid submersion for 24 hours was optimal for gelatin extraction. Those optimal condition has formed gelatin with more than 8% yields. It was considered great gelatin with 260.57 g Bloom of gel strength and 90.18% of emulsion stability. Sample gelatin has a quite reasonable acidity level at 4.5. Protein structures confirmation using the vibration of the best gelatin sample has also shown essential components such as O-H, N-H, and C=O on the FTIR spectrum.Keywords: chicken bones (Gallus domesticus), hydrochloric acid immersion, gel strength, emulsion stability, FTIR spectroscopy